Capacities of franchise networks and their influence on the form of governance - Narváez, Jamileth (2021)
Today the franchise is part of daily life for most consumers worldwide. A number of companies in different types of industries have adopted or think of franchising as a method of investing or doing business (Blair & Lafontaine, 2005). It is important to understand why so many companies that are dedicated to different economic activities have chosen the franchise format to market their products or services either within their own country or internationally. So, to understand the success of franchises, it is necessary to analyze their strategies. From the influence of authors such as Nelson & Winter (1994), Wenerfelt (1984), among others, the focus of competitive advantages shifted towards the internal aspects of a company, starting from the notion that companies are heterogeneous in their resources and capacities, competitive advantage becomes more dependent on internal exploitation. Applied to the franchise, this favored strategic management to focus on competitive advantage, giving greater importance to the role of network resources and capabilities as the fundamental basis of its governance strategy, which is what we will focus on.